Effect of Interactions on the Nutrient Status of a Tropical Soil Treated with Green Manures and Inorganic Phosphate Fertilizers - Abdul R. Bah; Zaharah A. Rahman; Aminuddin Hussin (The Scientific World Journal)
Integrated nutrient management systems using plant residues and inorganic P fertilizers have high potential for increasing crop production and ensuring sustainability in the tropics, but their adoption requires in-depth understanding of nutrient dynamics in such systems. This was examined in a highly weathered tropical soil treated with green manures (GMs) and P fertilizers in two experiments conducted in the laboratory and glasshouse. The treatments were factorial combinations of the GMs (Calopogonium caeruleum, Gliricidia sepium, and Imperata cylindrica) and P fertilizers (phosphate rocks [PRs] from North Carolina, China, and Algeria, and triple superphosphate) replicated thrice. Olsen P, mineral N, pH, and exchangeable K, Ca, and Mg were monitored in a laboratory incubation study for 16 months. The change in soil P fractions and available P was also determined at the end of the study. Phosphorus available from the amendments was quantified at monthly intervals for 5 months by 33P-32P double isotopic labeling in the glasshouse using Setaria sphacelata as test crop. The GMs were labeled with 33P to determine their contribution to P taken up by Setaria, while that from the P fertilizers was indirectly measured by labeling the soil with 32P. The P fertilizers hardly changed Olsen P and exchangeable cations during 16 months of incubation. The legume GMs and legume GM+P did not change Olsen P, lowered exchangeable Ca, and increased exchangeable K about threefold (4.5 cmol[+]kg−1 soil) in the first 4 months, even as large amounts of NH4-N accumulated (~1000 mg kg soil−1) and soil pH increased to more than 6.5. Afterwards, Olsen P and exchangeable Ca and Mg increased (threefold) as NH4+-N and soil pH declined. The legume GMs also augmented reversibly sorbed P in Al-P and Fe-P fractions resulting in high residual effect in the soil, while fertilizer-P was irreversibly retained. The GMs increased PR-P utilization by 40 to over 80%, mobilized soil P, and markedly enhanced uptake of N, K, Ca, and Mg. Thus GMs+PRs is an appropriate combination for correcting nutrient deficiencies in tropical soils.